2023
DOI: 10.1177/03009858231209410
|View full text |Cite
|
Sign up to set email alerts
|

PDL1 immunohistochemistry in canine neoplasms: Validation of commercial antibodies, standardization of evaluation, and scoring systems

Luisa Vera Muscatello,
Francesca Gobbo,
Giancarlo Avallone
et al.

Abstract: Immuno-oncology research has brought to light the paradoxical role of immune cells in the induction and elimination of cancer. Programmed cell death protein 1 (PD1), expressed by tumor-infiltrating lymphocytes, and programmed cell death ligand 1 (PDL1), expressed by tumor cells, are immune checkpoint proteins that regulate the antitumor adaptive immune response. This study aimed to validate commercially available PDL1 antibodies in canine tissue and then, applying standardized methods and scoring systems used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Furthermore, it is stated that cytoplasmatic PD-L1 cannot be reversed with commonly used anti-PD-L1 antibodies [ 73 ]. A recently published article on canine melanoma also follows the same score methodology, where only membranous staining was considered positive [ 74 ]. However, other recent studies regarding PD-L1 in canine melanoma considered both localizations as positive staining and reported that cytoplasmatic labeling was the most common [ 45 , 48 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is stated that cytoplasmatic PD-L1 cannot be reversed with commonly used anti-PD-L1 antibodies [ 73 ]. A recently published article on canine melanoma also follows the same score methodology, where only membranous staining was considered positive [ 74 ]. However, other recent studies regarding PD-L1 in canine melanoma considered both localizations as positive staining and reported that cytoplasmatic labeling was the most common [ 45 , 48 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Validation of commercial antibodies designed for human samples but with proven cross-reactivity for canine tissues may increase their availability for routine testing. While there are no specifically established evaluation methods for canine tumours, the extrapolation of human criteria has been used by Maekawa et al (2021) and Muscatello et al (2023) in several canine neoplasms [4,59]. In these studies, the PD-1/PD-L1 tumour proportion score (TPS; percentage of positive neoplastic cells) and combined positive score (CPS; percentage of positive cells, including immune cells, among total neoplastic cells) have been investigated [4,59].…”
Section: Pd/pd-l1 In Dogsmentioning
confidence: 99%
“…While there are no specifically established evaluation methods for canine tumours, the extrapolation of human criteria has been used by Maekawa et al (2021) and Muscatello et al (2023) in several canine neoplasms [4,59]. In these studies, the PD-1/PD-L1 tumour proportion score (TPS; percentage of positive neoplastic cells) and combined positive score (CPS; percentage of positive cells, including immune cells, among total neoplastic cells) have been investigated [4,59]. An alternative method, the immune cell density score (IDS), which considers the proportion of positive immune cells among all the cells in a specific area, has been reported [60].…”
Section: Pd/pd-l1 In Dogsmentioning
confidence: 99%
See 2 more Smart Citations